Repensar la educación y la pedagogía: algunas reflexiones críticas - Cascante Gómez, Lode E. (2008)
Certainly it becomes necessary to reflect on the school not only as a place of permanent cultural construction, influenced by multiple relationships, but also on how it becomes the place where these connections band together and set up new ones. In every analysis on education and pedagogies, it must not be left behind the fact that curricular designs explicit and condition the school practices. Likewise, these outlines also determine the intentionality of the teaching practices. These ideas constitute the basis guiding the reflections of this investigation, which more than appearing as theoretical issues, are actually visualized like practical possibilities. The arguments that are expressed here gather the most significant concerns conveyed by the authors. They account for the approximate outcome of the reading and the reflection on the personal teaching practice gained within the university classrooms and the experience of working with high school students.